2013
DOI: 10.1021/jp311563h
|View full text |Cite
|
Sign up to set email alerts
|

Ion Transport Effects in a Solid Polymer Electrolyte Due to Salt Substitution and Addition Using an Ionic Liquid

Abstract: We investigated mass and charge transport in amorphous salt-in-poly(ethylene oxide) (PEO) electrolytes with NaI and/or the ionic liquid (IL) EMImTFSI (1-ethyl-3-methylimizadolium bis(trifluoromethylsulfonyl)imide) as salt component. Combining the results of ion conductivity, pulsed field gradient nuclear magnetic resonance, and radiotracer diffusion measurements, it is found that over wide temperature ranges both the cation and anion diffusion coefficients and the charge diffusivity are distinctly larger in PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Recently, BCPs containing ionic liquids (ILs) have drawn attention as alternative electrolytes for lithium batteries . ILs are room temperature molten salts that are composed mostly of organic ions, offering several advantages including reduced flammability, low vapor pressure, good thermal stability, low toxicity, and good ionic conductivity . In 2007, He et al reported a method for preparing ion gels through the self‐assembly of PS‐PEO‐PS triblock copolymers at high IL, 1‐butyl‐3‐methylimidazolium hexafluorophosphate (BMIm‐PF 6 ), compositions for polymer electrolytes .…”
Section: Block Copolymer Electrolytes For Solid‐state Lithium Batteriesmentioning
confidence: 99%
“…Recently, BCPs containing ionic liquids (ILs) have drawn attention as alternative electrolytes for lithium batteries . ILs are room temperature molten salts that are composed mostly of organic ions, offering several advantages including reduced flammability, low vapor pressure, good thermal stability, low toxicity, and good ionic conductivity . In 2007, He et al reported a method for preparing ion gels through the self‐assembly of PS‐PEO‐PS triblock copolymers at high IL, 1‐butyl‐3‐methylimidazolium hexafluorophosphate (BMIm‐PF 6 ), compositions for polymer electrolytes .…”
Section: Block Copolymer Electrolytes For Solid‐state Lithium Batteriesmentioning
confidence: 99%
“…They observed an increase of the ion mobility as the temperature and the charge increased. Currently established concepts for determining ion conductivity of solid materials include impedance spectroscopy (IS), the radiotracer diffusion technique (RD), and pulsed field gradient nuclear magnetic resonance (PFG‐NMR) . IS relies on the ability to have two electrodes in contact with the sample, which in the case of nanoscale samples raises the problem of electrical short circuits.…”
Section: Introductionmentioning
confidence: 99%
“…The construction of separation and purification membranes for ions and molecules has also been studied using LbL films and related systems [29][30][31][32]. LbL films composed of poly(allylamine hydrochloride) (PAH) and poly(styrene sulfonate) (PSS), which were deposited on the surface of porous supports (pore diameter 20-200 nm), exhibited a high flux of monovalent ions while the flux of multivalent ions was significantly suppressed as a result of enhanced Donnan exclusion, as well as hindered diffusion in the film [33][34][35].…”
Section: Open Accessmentioning
confidence: 99%